Perencanaan Kawasan Wisata Jelajah Alam - Ramdan Yusuf (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2020)
The purpose of this research is to identify the planning of natural roaming tourism areas in Labengga Village, Galang District. The research method used is architectural design method by identifying data, both primary data and secondary data. The research procedure consisted of a ground tour, mini tour, and interviews. The results showed that based on the study of the planning approach, the location approach, the circulation concept, the parking concept, the concept of outdoor space, as well as structure and utility, the development of Labengga Village Nature Exploration is expected to be able to attract domestic and foreign tourists. The conclusion of this research is that the planning of a natural roaming tourism area in Labengga Village is a facility that offers an interesting function that contributes to a better environmental quality, especially in Tolitoli Regency.